Adherence to exclusive enteral nutrition by adults with active Crohn's disease is associated with conscientiousness personality trait: a sub‐study. Issue 6 (6th July 2020) - Wall, C. L.; McCombie, A.; Mulder, R.; Day, A. S.; Gearry, R. B.
Abstract: Background: It is probable that psychosocial factors predict adherence to exclusive enteral nutrition (EEN). Conscientiousness is an intrapersonal factor associated with greater medication adherence and healthy eating behaviours. This sub‐study aimed to determine whether adherence to EEN was associated with conscientiousness. Methods: Two groups of adults aged 16–40 years, were recruited to use EEN. Adults with active Crohn's disease used either EEN for 8 weeks or 2 weeks of EEN followed by 6 weeks of partial enteral nutrition (PEN). A control group of healthy adults used EEN for 2 weeks. Participants who reported eating food during EEN, ate more than one meal per day during PEN, or could not initiate or tolerate the oral nutritional supplements were defined as non‐adherent. Conscientiousness was measured using the conscientiousness subset of the Big Five Inventory. Results: Thirty‐eight patients with active Crohn's disease (mean age 24.8 years) and 21 healthy adults (mean age 27.3 years) completed the conscientiousness questionnaire. In the Crohn's disease group, 23 (59%) completed and adhered to the treatments compared to 17 (81%) healthy adults; their conscientiousness scores were similar. Adherence and completion by the Crohn's disease group were associated with a greater mean conscientiousness score 35.57 (95% confidence interval = 32.88–38.25) compared to 30.13 (95% confidence interval = 26.53–33.73) in the non‐adherent Crohn's disease group ( P  = 0.014). Conclusions: Conscientiousness was associated with treatment adherence. EEN can be a cognitively and emotionally demanding treatment for active adults with Crohn's disease; thus, considering personality traits may help determine suitable candidates. Abstract : Psychosocial factors probably predict adherence to medical nutrition therapies. Conscientiousness personality trait was associated with adherence to exclusive enteral nutrition therapy in adults with active Crohn's disease.